Effects of Silymarin on the Levels of Liver Enzymes and Hematological Parameters after Inguinal Hernia Repair: A Randomized Clinical Trial - Savari, Maryam; Beigi, Faramarz; Akhlaghi, Mahmood; Rafieian-Kopaei, Mahmoud; Kheiri, Soleiman; Heidari-Soureshjani, Saeid (Natural Products Journal, The, 2026)
Introduction/ObjectiveSurgery can lead to local and systemic activation of oxidative and inflammatory systems. Therefore, we aimed to evaluate the effects of silymarin on the levels of liver enzymes and hematological parameters after inguinal hernia repair.MethodsIn this randomized, double-blind clinical trial, 60 patients who were referred for hernia repair were included and randomly assigned into two groups. The intervention group was given silymarin three times a day, and the control group received a placebo. The patient's vital signs, hepatic enzymes, blood, and coagulation parameters were recorded before and after surgery. Data were analyzed by SPSSv18.Results and DiscussionHernia repair caused significant increases in the level of liver enzymes, White Blood Cells (WBC), Platelet Count (PLT), and Poly Morphonuclear Neutrophils (PMN) (p<0.05), but did not cause significant alteration in the level of coagulation factors, hematocrit (HCT) and hemoglobin (HB) (p>0.05). Supplementation of silymarin in patients significantly decreased the level of hepatic enzymes, WBC, PMN, LYMPH, and PLT (p<0.05). Furthermore, the results for vital signs, including Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), and PR were not changed after silymarin administration (p>0.05). Postoperative PTT levels in the intervention group were lower than those in the control group (p=0.023). Moreover, a significant difference was observed between the International Normalized Ratio (INR) of the two groups after surgery (p=0.039).ConclusionSilymarin supplementation has the ability to attenuate hepatotoxicity induced by surgery; however, further studies are needed to determine its exact mechanism of action.Registration Number1394-01-89-2449.
Keywords: hepatic enzymes